Characterization of the profile of vegetarian users who attend the University Restaurant of a public university, food practices and satisfaction with the preparations offered (Research, Society and Development, 2022)
The objective was to characterize the profile of vegetarian users who attend the University Restaurant (RU) of a public university, their eating habits and satisfaction with the preparations offered. This is a cross-sectional, qualitative and quantitative study, carried out via the internet, using a self-administered electronic questionnaire, with questions that covered the characterization of the studied population, lunch and dinner, consumption of certain foods and satisfaction with vegetarian protein preparations offered in the RU. The study included only RU users who answered “yes” to the question “Are you a vegetarian?” and who signed the Free and Informed Consent Form. Of the 662 participants, 67 (10.1%) claimed to be vegetarian, with a predominance of lacto-ovo vegetarians, the majority being female (82.1%) and more than half (56, 7%) in the age group between 20 and 24. There was a greater attendance of the vegetarian public at lunch (55.2%), with the price (82.0%) being the main reason to attend and the queue to get serve (25.4%) the most cited reason for not attending. Most of the population studied regularly consumed foods that are markers of healthy eating (MAS) and it was observed that 67.2% of vegetarians were dissatisfied with the vegetarian preparations offered. of this study pointed out that the RU constituted an environment that facilitated healthy eating practices and contributed to the maintenance of the health of vegetarian users; however, there is a need to develop strategies to increase users' satisfaction with the preparations offered.